Exploring Behavior Intention and Attitude Towards Adoption of Social Media of Nursing Student at School of Nursing Science at a Private University, Thailand - Achwarin, Dr Naree; Boonto, Chavalee; Praewanich , Prapawan; Saw Yu Thanda (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
The study aimed to determine the behavioral intention to adopt the social media as supplementary tool, investigate the attitude towards adoption of social media as supplementary tool, and explore how the nursing students adopt the social media as supplementary tool for Nursing Foundation course of nursing student at a private university. The researchers used mixed research design, quantitative research and qualitative research method. The survey questionnaire with 5 Likert Scale was employed for quantitative research to measure the behavior intention to adopt the social media as supplementary tool for Nursing Foundation course and attitude towards adoption of social media and semi structure questionnaire for qualitative research. The participants of the study who completed and returned the survey were 24 nursing students. The semi - structure questionnaire was employed to explore how the nursing student adopted the social media as supplementary tool for Nursing Foundation course at a private university, The researchers utilized the descriptive statistic to analyze the data for quantitative research and content analysis, inductive and deductive method for the qualitative research. The research findings revealed that the student perception towards all 5 variables were at high level. However; the student perception toward perceive ease of use (PEU) was the highest level (=4.67,S.D.=0.71) among all five variables, Perceive usefulness (PU) was at high level (=4.35.,S.D.= 0.58) , the student attitude toward using(ATU) social media was at high level (=4.16,S.D.=0.51) , the student’s satisfaction was positive attitude at high level ( .,S.D.=0.95) and the student behavioral intention (BI) toward adoption of social media was at high level consecutively at ( 3.92.,S.D.=0.73).